EVALUASI PENERAPAN TAX PLANNING DALAM UPAYA MENINGKATKAN EFISIENSI PEMBAYARAN BEBAN PAJAK PENGHA-SILAN DAN PAJAK PERTAMBAHAN NILAI PADA PT. AAI - Devi Yanti; Jesica Handoko; S, Patricia Febrina Dwijayanti (Jurnal Akuntansi Kontemporer, 2020)
Tax planning is the process of organizing a business taxpayer that his tax debt, both income tax and other taxes, is in a posi-tion most minimal, all in accordance with the provisions of the tax laws as well as commercially. Accordingly, this study will evalu-ate the implementation of tax planning that has been done by PT. AAI as aluminum distributor company in Surabaya, in an effort to improve the efficiency of the burden of payment of Income Tax and Value Added Tax in accordance with prevailing tax regula-tions during 2012. Among the rules it is Law. 36 Year 2008 on Income Tax and Law. 42 Year 2009 on Value Added Tax. During this time , the implementation of tax planning efforts conducted by PT. AAI is not optimal. This research is a descriptive study with a case study approach. The data used in this study is qualitative data in the form of data that contains the condition of the company and quantitative data in the form of data in the form of documents, or the list of numbers that can be calculated. The data obtained from literature and field studies obtained through observation, interviews, and documentation. The results of the study showed that the costs incurred by the company and included in the Commercial Income Statement are not all included in the Fis-cal Income Statement and exempt income included as an addition to income tax. In addition, tax planning VAT is also not optimal because of the outstanding customer receivables can affect VAT payments and payments related to the effort creditable input VAT charged but not included. The evaluation results showed the company can improve the efficiency of the payment burden of Rp 8,358,357.00 Income Tax and Value Added Tax of Rp 1,073,209.00.